Digitalization for Energy Access in Sub-Saharan Africa : Challenges, Opportunities and Potential Business Models - Davide Mazzoni (Fondazione Eni Enrico Mattei (FEEM), 2019)
Innovative business models supported by digital technologies, together with the widening connectivity and data collection, are already giving a big contribution in fostering the access to electricity and clean cooking in Sub-Saharan Africa. This paper gives an overview on the actual state of energy access in Sub-Saharan Africa and the current technologies used to provide it, followed by a description of the key trends and drivers of the ongoing African digital transformation. A deep analysis of the Pay-as-you-go business model in the off-grid solar sector will shed light on how this transformation started some years ago and the way it is affecting society in many ways. Strengths and opportunities — as well as weaknesses and risks of the model — are provided through a screening of the most representative business experiences in East and West Africa, financial aspects and market analysis. The perspective of both companies and end-users have been considered here. The last section gives recommendations to policy-makers on how to ride the wave of digitalization to foster the access to clean and reliable energy, by acting on the electrification planning, regulations, business environment, distribution channels and mobile money environment.
Keywords: O13; O33; O55; M13; Q40; Q48; 330; Energy Access; Digitalization; PAYGO; Business Models; Africa; Digital Transformation